Answer:
Slope, m =
.
Explanation:
The slope of the line can be determined by simplifying the given equation to its standard form.
In the standard form, y = mx + c, m represents the slope of the line.
We are given:
![$ y - 2 = - (2)/(3)(x + 1) $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/au5d36i6usoilxj2duc7akzyokehk17r88.png)
![$ \implies y = -(2)/(3)x - (2)/(3) + 2 $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xb6wg5ko8ehvzivf1umoeqzapc5ecbjq6x.png)
![$ \implies y = - (2)/(3)x + ((-2 + 6))/(3) $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qrs8noa9wmzzpyzdv0qwo9we3wn0fi36qd.png)
![$ \implies y = -(2)/(3)x + (4)/(3) $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8hrciyvmrldbdoohuege3cud608o4ev2da.png)
Comparing it with the standard equation, we can see that the slope, m =
.
Hence, the answer.